Influence of body condition score and its change after parturition on pregnancy rates to fixed-timed artificial insemination in Bos indicus beef cows - Carvalho, R. S. [UNESP]; Cooke, R. F.; Cappellozza, B. I.; Peres, R. F.G. [UNESP]; Pohler, K. G.; Vasconcelos, J. L.M. [UNESP] (My University, 2022)
This experiment evaluated pregnancy rates to fixed-time artificial insemination (FTAI) in Bos indicus beef cows according to their body condition score (BCS) at calving and subsequent change until 30 days after FTAI. Non-pregnant, suckling Nelore cows (n = 593 primiparous, 461 secundiparous, and 893 multiparous) were evaluated for BCS at calving and FTAI, and at 30 days after FTAI when cow pregnancy status was verified. Cow BCS at calving was subtracted from BCS recorded at pregnancy diagnosis, and cows classified as those that lost BCS (L), maintained BCS (M), or gained BCS (G) during this period. Cows that calved with BCS ≥ 5.0 had greater (P < 0.01) BCS throughout the experiment, and greater (P < 0.01) pregnancy rates to FTAI compared with cows that calved with BCS < 5.0 (54.8 vs. 34.2%). Pregnancy rates to FTAI were greater (P < 0.01) for G and M cows compared with L cows (50.0%, 47.5%, and 36.0%, respectively), and similar (P = 0.46) between G and M cows. Moreover, pregnancy rates to FTAI in G cows that calved with BCS < 5.0 were less compared with L (tendency; P = 0.08) and M cows (P < 0.01) that calved with BCS ≥ 5.0 (42.2%, 48.3%, and 58.3%, respectively). In summary, pregnancy rates to FTAI were greater in B. indicus cows that calved with a BCS ≥ 5.0 regardless of parity and post-calving BCS change, and greater in M and G cows within those that calved with BCS < 5.0 or ≥ 5.0.
Keywords: Beef cows; Body condition score; Fixed-time artificial insemination; Pregnancy